Development of Multiwalled Carbon Nanotube-Reinforced Biodegradable Polylactic Acid/Polybutylene Succinate Blend Membrane - Badar M. AlruwailI; Usman Saeed; Iqbal Ahmad; Hamad Al-Turaif; Hani Aboalkhair; Abdulmohsen O. AlsaiarI (Membranes, 2021)
Currently, gas separation (GS) membranes are produced from petrochemical-based polymers, but their lifespan is severely impacting the environment. Therefore, there has recently been growing interest in developing ecofriendly biodegradable polymer-based GS membranes. This study developed a polylactic acid (PLA)/polybutylene succinate (PBS) blend composite membrane for GS using the dry/wet phase inversion technique. The influence of the multiwalled carbon nanotube (MWCNT) concentration in the PLA/PBS blend was studied by investigating tensile properties, porosity, percentage crystallinity, contact angle, and gas permeance.The obtained results demonstrate that the addition of MWCNT enhances the tensile strength, porosity, and percentage crystallinity, whereas it decreases the contact angle. The pure gas permeation was investigated at pressures of 2–4 bar at 25 °C. The gas permeation study revealed that the PLA/PBS blend with 0.5% wt. MWCNT enhanced the gas permeance and selectivity at 4 bar. The gas permeance acquired at 25 °C and 4 bar for PLA/PBS reinforced with MWCNT was highest in hydrogen followed by carbon dioxide, argon, and nitrogen. Additionally, a study of the membrane morphology illustrated the uniform dispersion of MWCNT in the PLA/PBS blend. The investigation concluded that membranes containing MWCNT are capable of separating gases at the molecular level, thereby reducing energy consumption.